ANALISIS KEPATUHAN SYARIAH PADA RELIANCE LIFE UNIT SYARIAH - Rani Ramadhani, (2022)
The development of sharia insurance in Indonesia raises the question of how the form of compliance with sharia principles (sharia compliance) is carried out by the company. Shariah compliance is considered to be the basis for distinguishing between sharia and conventional financial institutions. Therefore, this study aims to find out how the operational activities are carried out by Reliance Life Unit Syariah, as well as the form of implementation of shariah compliance which is carried out by referring to the dimensions and provisions of shariah compliance in terms of DSN MUI Fatwa No:21/DSN -MUI/X/2001. This study uses qualitative research methods with data collection techniques through interviews, non-participant observation, and documentation. After that, the researchers used data triangulation techniques to test the validity of the data, then carried out data reduction, data presentation and data verification to analyze the data. The results of the study show that Reliance Life Unit Syariah Sharia Business Unit has implemented shariah compliance in its operational activities. The researcher found that the activities carried out were in accordance with the DSN-MUI Fatwa Number 21/DSN-MUI/X/2001 and the fatwas and other regulations governing sharia insurance.